Epidemiology of physical inactivity in Nigeria: a systematic review and meta-analysis. (13th May 2021) - Adeloye, Davies; Ige-Elegbede, Janet O; Auta, Asa; Ale, Boni M; Ezeigwe, Nnenna; Omoyele, Chiamaka; Dewan, Mary T; Mpazanje, Rex G; Agogo, Emmanuel; Alemu, Wondimagegnehu; Gadanya, Muktar A; Harhay, Michael O; et al.
Abstract: Background: Physical activity is crucial to preventing noncommunicable diseases. This study aimed to provide up-to-date evidence on the epidemiology of insufficient physical activity across Nigeria to increase awareness and prompt relevant policy and public health response. Methods: A systematic literature search of community-based studies on physical inactivity was conducted. We constructed a meta-regression epidemiologic model to determine the age-adjusted prevalence and number of physically inactive persons in Nigeria for 1995 and 2020. Results: Fifteen studies covering a population of 13 814 adults met our selection criteria. The pooled crude prevalence of physically inactive persons in Nigeria was 52.0% (95% CI: 33.7–70.4), with prevalence in women higher at 55.8% (95% CI: 29.4–82.3) compared to men at 49.3% (95% CI: 24.7–73.9). Across settings, prevalence of physically inactive persons was significantly higher among urban dwellers (56.8%, 35.3–78.4) compared to rural dwellers (18.9%, 11.9–49.8). Among persons aged 20–79 years, the total number of physically inactive persons increased from 14.4 million to 48.6 million between 1995 and 2020, equivalent to a 240% increase over the 25-year period. Conclusions: A comprehensive and robust strategy that addresses occupational policies, town planning, awareness and information, and sociocultural and contextual issues is crucial to improving physical activity levels in Nigeria.